DICER1: A Key Player in Rheumatoid Arthritis, at the Crossroads of Cellular Stress, Innate Immunity, and Chronic Inflammation in Aging - De Cauwer, Aurore; Mariotte, Alexandre; Sibilia, Jean; Bahram, Seiamak; Georgel, Philippe (Frontiers in Immunology, 2018)
Loss-of-function or knock-out mouse models have established a fundamental role of the RNAse III enzyme DICER1 in animal development and tissue morphogenesis and/or homeostasis. These functions are currently assumed to result mainly from the DICER1-dependent biogenesis of microRNAs (miRNAs) which exhibit important gene expression regulatory properties. However, non-canonical DICER1 functions recently emerged, such as interacting with the DNA-Damage Response (DDR) pathway and the processing of cytotoxic non-coding RNAs, suggesting that DICER1 might also participate in the regulation of major cellular processes through miRNAs-independent mechanisms. Recent findings indicated that reduced Dicer1 expression, which correlates with worsened symptoms in mouse models of joint inflammation, is also noted in fibroblast-like synoviocytes (FLS) harvested from rheumatoid arthritis (RA) patients, as opposed to FLS cultured from biopsies of osteoarthritis patients. In addition, low DICER1 levels are associated to the establishment of cellular stress and its associated responses, such as cellular senescence. Senescent and/or stressed cells are associated with an inflammatory secretome (cytokines and chemokines), as well as with “find-me” and “eat-me” signals which will attract and activate the innate immune compartment (NK cells, macrophages and neutrophils) in order to be eliminated. Failure of this immunosurveillance mechanism and improper restauration of homeostasis could lead to the establishment of a systemic and chronic inflammatory state. In this review, we suggest that reduced DICER1 expression contributes to a vicious cycle during which accumulating inflammation and premature senescence, combined to inadequate innate immunity responses, creates the appropriate conditions for the initiation and/or progression of autoimmune-autoinflammatory diseases, such as RA.